2013
DOI: 10.1038/nchembio.1333
|View full text |Cite
|
Sign up to set email alerts
|

Small-molecule antagonists of melanopsin-mediated phototransduction

Abstract: Melanopsin, expressed in a subset of retinal ganglion cells, mediates behavioral adaptation to ambient light and other non-image forming photic responses. This has raised the possibility that pharmacological manipulation of melanopsin can modulate several CNS responses including photophobia, sleep, circadian rhythms and neuroendocrine function. Here we describe the identification of a potent synthetic melanopsin antagonist with in vivo activity. Novel sulfonamide compounds inhibiting melanopsin (opsinamides) c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
63
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(66 citation statements)
references
References 32 publications
3
63
0
Order By: Relevance
“…The involvement of ipRGCs in photophobia has been described in mice. [24][25][26] It has been confirmed that the pupil diameter increases when ipRGC and rod excitation is at a minimum. 27 Furthermore, there is strong evidence of an inhibiting influence of S-cones on ipRGCs.…”
Section: Discussionmentioning
confidence: 61%
“…The involvement of ipRGCs in photophobia has been described in mice. [24][25][26] It has been confirmed that the pupil diameter increases when ipRGC and rod excitation is at a minimum. 27 Furthermore, there is strong evidence of an inhibiting influence of S-cones on ipRGCs.…”
Section: Discussionmentioning
confidence: 61%
“…Previous studies have found the absorption maxima of purified melanopsins and the maximal spectral sensitivity of melanopsin-expressing cultured cells are both around 480 nm (13, 14, 16 -21). Although some G q -independent signaling by melanopsin has been suggested (22), a variety of melanopsins are reported to show light-dependent G q activation in vivo and in vitro (14,17,18,(23)(24)(25)(26), consistent with their high sequence similarity with the invertebrate visual pigments, which also use G q -dependent signaling (7,9) (Fig. 1A).…”
mentioning
confidence: 53%
“…Because melanopsins are coupled with G q -type G proteins, light-dependent G q activation by melanopsin can be detected as an increase in the Ca 2ϩ -activated Cl Ϫ current (14, 39,40). To detect the difference in the retinal release rate from melanopsin, melanopsin-expressing oocytes were treated with retinal and subsequently incubated at 37°C in the dark for 90 min in the presence or absence of a melanopsin-specific antagonist AA92593 (24). A previous study has shown that the antagonist can bind to the retinal-free form of melanopsin and block retinal binding to the protein, leading to reduction of light-dependent current by melanopsin (24).…”
Section: Retinal Release From Melanopsin Molecules In Cell Membranesmentioning
confidence: 99%
“…Indeed, it has been suggested that the mood stabilizer lithium may have a circadian mechanism of action [97], and casein kinase 1δ/ε inhibitors have shown promise in pre-clinical animal models of AUD [121] and BD [122]. Additional compounds have been developed to target the ROR/REV-ERB nuclear receptors [123], CRYs [124], melanopsin-containing photoreceptors [125] and other complex mechanisms [123] that strongly affect circadian rhythms, but remain poorly characterized with respect to brain effects and potential as treatments for psychiatric conditions. Suppression of GC synthesis with metyrapone counteracts the elevations in GC levels associated with environmental changes, and accelerates the clock's adaptation, potentially offering the means to better adjust the circadian system to stressful environments [23].…”
Section: Discussionmentioning
confidence: 99%